CrCpTp: a high-spin Cr(II) sandwich complex with a large structural distortion. - Brunker, T; Green, J; O'Hare, D (2002)
CrCpTp was synthesized from the reaction of [CrCpCl](2) and KTp. Magnetic measurements indicate it to have a high-spin (S = 2) electronic configuration from 5 to 300 K. A single-crystal X-ray study reveals bond lengths typical for a high-spin configuration and a pronounced Jahn-Teller distortion. The nature of this distortion was probed by DFT calculations and the variation in bond lengths successfully reproduced. The metal-based HOMO is significantly antibonding with respect to a single pyrazolyl ring only.